1995
DOI: 10.1152/jappl.1995.79.5.1640
|View full text |Cite
|
Sign up to set email alerts
|

Myoneural interactions affect diaphragm muscle adaptations to inactivity

Abstract: We hypothesized that inactivity effects on diaphragm muscle contractile and morphometric properties are attenuated if phrenic motoneurons are also inactive. Three models of rat diaphragm inactivity were compared: 1) spinal isolation; 2) tetrodotoxin (TTX) nerve blockade; and 3) denervation (Dnv). Motoneuron and muscle fiber inactivities were matched only in spinal isolated animals. After 2 wk, maximum tetanic force decreased in all three groups compared with control group but to a greater extent in TTX and Dnv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
229
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(256 citation statements)
references
References 0 publications
24
229
2
Order By: Relevance
“…8,9,11,12,14,21 Briefly, the cervical spinal cord was exposed with a bilateral dorsal laminectomy at C2, and the right anterolateral cord was transected at C2 (i.e., involving the lateral and ventral funiculi, and preserving the dorsal funiculus). All animals were observed daily after surgery, and intramuscular buprenorphine and oral acetaminophen were administered for the first 3 days.…”
Section: Shmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,11,12,14,21 Briefly, the cervical spinal cord was exposed with a bilateral dorsal laminectomy at C2, and the right anterolateral cord was transected at C2 (i.e., involving the lateral and ventral funiculi, and preserving the dorsal funiculus). All animals were observed daily after surgery, and intramuscular buprenorphine and oral acetaminophen were administered for the first 3 days.…”
Section: Shmentioning
confidence: 99%
“…All SH animals displayed gross deficits related to the cervical spinal cord injury such as altered movements of the rib cage and abdomen consistent with hemidiaphragm paralysis. 8,9 Histological evidence of transplanted MSCs survival…”
Section: Intraspinal Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficacy of force generation and shortening would be impaired. Accordingly, it was observed that following denervation of the rat diaphragm muscle specific force was reduced and Vmax was slowed [52].…”
Section: Myhc-iixmentioning
confidence: 99%
“…In our previous studies 23) , after 2 weeks of unilateral diaphragm muscle paralysis induced by SPH, there was only a small decrease in muscle-specific force, and no change in the maximum unloaded shortening velocity. In contrast, after DNV or TTX blockade, there was a marked decrease in specific force and a substantial slowing of maximum unloaded shortening velocity in the diaphragm muscle.…”
Section: Inactivity-related Changes In Diaphragm Musclementioning
confidence: 71%